Sources, pathways, and abatement strategies of macroplastic pollution: an interdisciplinary approach for the southern North Sea - Meyerjürgens, Jens; Ricker, Marcel; Aden, Christian; Albinus, Michelle; Barrelet, Johna; Freund, Holger; Hahner, Florian; Lettmann, Karsten A.; Mose, Ingo; Schaal, Peter; Schöneich-Argent, Rosanna I.; Stanev, Emil V.; et al. (Frontiers in Marine Science, 2023)
The issue of marine plastic pollution has been extensively studied by various scientific disciplines in recent decades due to its global threat. However, owing to its complexity, it requires an interdisciplinary approach to develop effective management strategies. The multidisciplinary scientific approach presented here focuses on understanding the sources and pathways of macroplastic litter and developing abatement strategies in the southern North Sea region. Over 2.5 years, more than 63,400 biodegradable wooden drifters were deployed with the help of citizen science to study the sources, pathways, and accumulation areas of floating marine litter. Rivers act as sinks of most of the floating marine litter released within their waterways. Short-term field experiments were also conducted to analyse the hydrodynamic and atmospheric processes that govern the transport of floating litter particles at the sea surface. Numerical models were used to examine the transport of virtual litter particles in the entire North Sea and in coastal regions. It was found that there are no permanent accumulation areas in the North Sea, and the Skagerrak and fronts can increase the residence times of floating marine litter and favour sinking. Field surveys revealed that the majority of litter objects originate from fisheries and consumer waste. To develop effective abatement strategies, the key stakeholder landscape was analysed on a regional level. The interdisciplinary approach developed in this study highlights the importance of synergizing scientific resources from multiple disciplines for a better understanding of marine plastic pollution and the development of effective management strategies.